INOVASI PRODUK DAN HARGA SEBAGAI UPAYA DALAM MENINGKATKAN MINAT BELI HANDPHONE VIVO DI TOKO MYCELL - Syafruddin, S; Julianti, Rini (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to determine the effect of product innovation and price in increasing interest on purchasing Vivo cellphones at the Mycell Store. The type of this study was associative study which aims to examine the effect of product innovation (X1) and price (X2) on Vivo cellphones purchasing interest at the Mycell Store (Y). The type of data used in this study was quantitative data obtained directly from research respondents using a questionnaire. Respondents in this study were consumers who purchased Vivo brand mobile phones at the Mycell Store, totaling 71 people, who were determined using probability sampling techniques with the simple random sampling method. The data used in this study were processed with SPSS software for analysis using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient testing (R2). The results of this study showed that partially product innovation had a positive and significant effect on Vivo cellphones purchasing interest, while price had a negative and significant effect on Vivo cellphones purchasing interest at the Mycell Store. In simultaneously, product innovation and price had a significant effect on Vivo cellphones purchasing interest at the Mycell Store. The effect of product innovation and price on Vivo cellphones purchasing interest at the Mycell Store was 72.1%, while the remaining of 27.9% was effected by other factors not included in this study, such as store location, service quality, and product completeness.